PENINGKATAN KREATIFITAS DAN KOMPETENSI BELAJAR SISWA MENGGUNAKAN PEND,EKATAN KONTEKSTUAL PADA MATERI PELAJARAN EKOSISTEM DI SMA NEGERI 1 ANGKOLA BARAT - Fitri Agustina Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The Process of Improving the Creativity and Competence of Student Learning Using a Contextual Approach to the Material Class Ecosystem X1 SMA Negeri 1 Angkola Barat”. Thesis. Graduate Program of Padang State University. This research is based on the problem of low creativity and competence of students in learning biology. From the daily tests, creativity and competence of students are still learning under (KKM) minimum criteria of a passing grade. Data were obtained from qualitative and quantitative data. Qualitative data were collected through observation, field notes, and interviews. Quantitative data were obtained through cognitive tests, observation creativity, affective and psychomotor competencies. The was an analysis of the data used qualitative descriptive and statice technique. The result shows that the use of a contextual approach toward the ecosystem material can enhance creativity and learning competencies. The increase can be seen in each aspect of the creative learning, affective and psychomotor competencies ranging from pre-cycle, the first cycle, and second cycle. This increase is also seen in the results of the exam pre cycle ie, 61.80 in the first cycle, 66.66 and the second cycle 88.88. Based on the results, it can be concluded that contextual approach can improve the creativity and competence of students of class X1 Angkola Barat.Keywords: Contextual, Creativity, and Competence.